2D-organic framework confined metal single atoms with the loading reaching the theoretical limit. Issue 10 (25th August 2020) - Lin, Chao; Zhang, Hao; Song, Xiaokai; Kim, Dong-Hyung; Li, Xiaopeng; Jiang, Zheng; Lee, Jung-Ho
Abstract : A synthetic strategy utilizing a predesigned organic framework is demonstrated to construct high-density single-atom catalysts for long-lasting zinc–air flow batteries. Abstract : Precise synthesis of single-atom catalysts (SACs) with a homogeneous coordination environment and high metal loading remains a great challenge. Here, for the first time, we demonstrate the preparation of cobalt single atoms with an ultra-high metal loading of 20.5 wt% based on the two-dimensional conjugated organic framework of C2 N. The porous framework of C2 N provides confined space for trapping metal atoms and inhibiting metal aggregation, while the skeleton provides pairs of pyridinic nitrogens as coordination sites to immobilize metal atoms. The as-prepared catalyst exhibited bifunctional activity toward the oxygen reduction and oxygen evolution reactions (ORR and OER). The corresponding rechargeable zinc–air flow battery shows remarkable stability with no degradation even after continuous operation for 6000 cycles (equivalent to 1000 h), placing it as one of the most long-lasting zinc–air batteries. This confined synthetic strategy can be generalized to construct SACs of other metals with different element combinations.